Participation in Church or Religious Groups and its Association with Health: A National Study of Young Canadians - Michaelson, Valerie (Springer US, 2013)
The purpose of this study was to determine how participation of young Canadians in a church or religious group correlated with holistic health indicators. Health was viewed in terms of risk and protective behaviors, outward looking prosocial behaviors, and measures of internal feelings, with the composite picture of health connecting to the Hebrew concept of shalom. A separate analysis of sports-involved children was used as a comparator. Children involved in religious groups reported lower participation in risk behaviors, higher prosocial behaviors, but poorer levels of the more holistic measures of health. Sports-connected youth reported more positive holistic measures of health and some increases in overt risk-taking. Our findings raise theological and practical issues regarding how the church understands itself and lives out its mission. They suggest an emphasis on teaching about behaviors and morality rather than an understanding of shalom that is grounded in the Incarnation and in the deeply integrative nature of the Christian life.